Epistemologi Pengajaran Tauhid pada Tingkat Dasar: Prioritas Wahyu di atas Akal dalam Pembentukan Sumber Ilmu Santri SMP Pesantren Imam Bukhari - Mujiburrohman, Mujiburrohman; Alfajri, Hamzah (TSAQOFAH, 2026)
This study aimed to conduct an in-depth analysis of the epistemology of Tauhid instruction for first-year junior high school santri at Pesantren Imam Bukhari, with a focus on the principle of prioritising revelation (naqli) over reason (‘aqli) as the primary source of truth. Using a qualitative method with a case study approach, data were collected through interviews with three akidah teachers, observations of the teaching–learning process, and analysis of curriculum documents. The findings show that the pesantren’s epistemology consistently establishes revelation as the highest authority (ḥujjah), which at the basic level is instilled through the use of simple pedagogical analogies and an emphasis on obedience in religious practice rather than philosophical debate. The assertion of the priority of revelation has axiological implications for the formation of early disciplinary character and absolute obedience (taslīm) to religious teachings, which serves as a foundation for future steadfastness in creed (istiqāmah). These findings affirm that developing an epistemology of Tauhid instruction grounded in the priority of revelation for junior high school santri plays a strategic role in building the foundations of faith and early obedience within the context of pesantren education.